(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
During the years of independence, large-scale work is being carried out in Uzbekistan to develop the quality of construction and improve the achievement of economic efficiency. The consistent implementation of important priorities, programs and projects on the development of infrastructure facilities in our republic is the development of modern construction in cities and districts, including rural areas. In the Republic of Uzbekistan, great attention is paid to the development of a national-innovative system in the production of building materials, objects and structures, ensuring the required growth rates of modern construction and the development of the construction industry. This article provides relevant instructions on the problems that the materials used in the reinforcement of reinforced concrete structures face in them, and of course on modern solutions.